Socialization of Technology Utilization and Tax Modernization at SMK N 1 Medan - Yunita Sari Rioni; Tia Novira Sucipto; Oktarini Khamilah Siregar; Anwar Suhut (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
The community service activity with the title "Socialization of Technology Utilization and Tax Modernization at SMK Negeri 1 Medan" was carried out well and smoothly. The participation and interaction of the participants in this activity greatly support the success of the activities that have been carried out. Basically, this community service activity is carried out to contribute to the field of education related to taxation.